Supporting about ‘education’ in elementary School: A review of literature - Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This research aims to analyze a review of literature about education in elementary school. Aside from historical changes, the study aims to investigate the intricate, overt and covert deliberate manipulations of this behavior for paranoid reasons. It also looks into the terrible treatment they received as a result of the deadly coronavirus pandemic, also known as the research community's term for learning loss. In this study, data gathering strategies such as documentation were employed, as well as data analysis techniques such as data collection, data display, data reduction, data analysis, and data conclusion. Islamic education has three obstacles in the globalization era: cultural globalization challenges, low levels of social capital challenges, and structural and cultural challenges.